NILAI DIDAKTIS SUMPAH HARI CANDANI SEBAGAI SUMPAH PEMUTUS DALAM PERKARA PERDATA (STUDI KASUS DI PENGADILAN NEGERI GIANYAR) - I Wayan Sudarma; I Nengah Duija; I Putu Gede Parmajaya (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
This study is about how the didactic values contained in the implementation of the Candani Day oath as the Breaking Oath in a civil case at the Gianyar District Court Number: 148/Pdt.G/2016/PN.Gin., dated 18 November 2016. submitted before and for disputes, the second party to the dispute decides to take the Candani Day oath or the Cor Oath at Ulun Kulkul Besakih Temple, Karangasem. The method used in this research is descriptive qualitative with a naturalistic approach of a case study (case study) design of a single case study design (single case study). This research data collection technique is a technique; observations, unstructured interviews, literature studies and document studies which were then analyzed by data analysis techniques using the Miles and Huberman model. This research was conducted before checking the validity of the conclusion data from source triangulation and technical triangulation. The results of this study show that Hari Candani's oath as a severing oath in civil cases at the Gianyar District Court is carried out according to the Hindu religion and according to the procedures (traditions) of the Balinese indigenous people. The implementation of the oath functions as: 1) honesty education, 2) sportsmanship education, 3) increasing sraddha and devotion of Hindus, 4) education for justice and legal certainty and, 5) the role of religion for justice and legal certainty. Meanwhile, the didactic value of Hari Candani's oath as a severing oath in civil cases is; 1) divinity values, 2) moral values (decency), 3) the value of justice before the law and, 4) the value of legal certainty.Keywords: Candani Day Oath, Breaking Oath in the Civil Code, Didactic Values